Anti- Anaplasma spp antibodies in a population at occupational risk of a veterinary hospital - Weinborn A., Romy (2018)
The objective of this study was to estimate the seroprevalence of antibodies against Anaplasma spp in students and staff of the Teaching Veterinary Clinical Hospital (HCVD) of the School of Veterinary Medicine of the University Santo Tomás (UST), Talca, Chile. Blood samples (n=58) were collected and analyzed by indirect immunofluorescence (IFI) for IgG. The exact Fischer or X2 test was used to evaluate significant differences (p<0.05) and the Kappa index to evaluate concordance between IFI and clinical signology. The results showed 25.9% of  seropositivity among students and staff for Anaplasma spp. Significant differences were found in the use of biosecurity measures, extraction of ticks, and ectoparasite findings in clothing. The Kappa index was 0.13.